REHABILITATION OF PATIENTS AFTER CARDIAC SURGERY - Romaniuk, T. V.; Moroz, V. S.; Maslii, S. M.; Vivchar, Z. V. (International Journal of Medicine and Medical Research, 2022)
Background. Patients undergoing cardiac surgery are under a high risk of post-operative reductions in respiratory muscle strength and pulmonary function as well as lowered functional capacity. In-hospital physical inactivity and inappropriate rehabilitation increases the chances for development of these complications and affects patients’ future independence in daily routine. Cardiac rehabilitation is crucial in preventing complications and assisting the early function recovery. However, despite the evidences for its benefits and strong guideline recommendations, the uptake of cardiac rehabilitation remains poor. Objective. this study is aimed at promotion of cardiac rehabilitation and sharing successful experience of using it. Methods. Post-surgical treatment and rehabilitation of 387 patients with cardiovascular pathology in the Department of Vascular and Cardiac Surgery of Municipal Non-Commercial Enterprise “Ternopil Regional Clinical Hospital” of Ternopil Regional Council has been analysed. Results. The experience of successful post-surgical treatment and rehabilitation allowed establishing the basic approaches to perioperative management of patients with cardiovascular surgical pathology. Key principles include minimized ICU stay and artificial ventilation time, early verticalization and beginning of physical activities, early removed drainage tubes, tracheobronchial tree drainage, nutritional balance, lymphatic drainage massage, application of elastic jersey on the lower extremities, early transferring to the surgery ward and returning to the regular daily activities, circumstantial health education, complex work of a multidisciplinary team. Conclusions. This set of rehabilitation measures helps prevent complications after cardiac surgery as well as provide a faster patient’s daily routine.